Organised crime, trafficking, drugs: selected papers presented at the Annual Conference of the European Society of Criminology - Nevala, Sami; Aromaa, Kauko (Publication series, 2004)
In the 2003 annual conference of the European Society of Criminology (ESC) in Helsinki (27–30 August), quite a large number of papers (21) were presented that focused on issues related to organised crime, including trafficking in human beings and corruption. This collection presents all of these papers to the benefit of those who attended and, in particular, those who did not. During the conference, many colleagues expressed the feeling that such material should be made more widely available than was possible at the conference alone